Public-Private Partnership’s Contract in Malaysia: Some Areas of Concern in a Land Swap Arrangement - Suzana Muhamad Said (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
AbstractThis paper seeks to explore the public-private partnership initiative and salient provisions of government contracts in Malaysia. This paper further examines some areas of concern emphasising on a land swap type of contract. There are still many other provisions that need to be addressed for example on obligations, design and constructions, choosing the right type of contracts, operations and maintenance, sub-contracts, relief events, liability and damages, performance security, default and termination and dispute resolutions which is not dealt in this paper.